2021
DOI: 10.3390/toxins13120913
|View full text |Cite
|
Sign up to set email alerts
|

rDromaserpin: A Novel Anti-Hemostatic Serpin, from the Salivary Glands of the Hard Tick Hyalomma dromedarii

Abstract: Hemostatic disorders are caused either by platelet-related dysfunctions, defective blood coagulation, or by a combination of both, leading to an increased susceptibility to cardiovascular diseases (CVD) and other related illnesses. The unique specificity of anticoagulants from hematophagous arthropods, such as ticks, suggests that tick saliva holds great promise for discovering new treatments for these life-threatening diseases. In this study, we combined in silico and in vitro analyses to characterize the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
(110 reference statements)
0
5
0
1
Order By: Relevance
“…It also inhibits kallikrein, FXIa, and to a lesser extent FXIIa, but has no significant effect on other factors. Recombinant dromaserpin also blocks thrombin‐induced platelet aggregation [117].…”
Section: Inhibition Of Coagulationmentioning
confidence: 99%
“…It also inhibits kallikrein, FXIa, and to a lesser extent FXIIa, but has no significant effect on other factors. Recombinant dromaserpin also blocks thrombin‐induced platelet aggregation [117].…”
Section: Inhibition Of Coagulationmentioning
confidence: 99%
“…Es inhibiert auch Kallikrein, FXIa und in geringem Maße FXIIa, hatte aber keine signifikante Wirkung auf andere Faktoren. Rekombinantes Dromaserpin blockierte auch die Thrombin-induzierte Thrombozytenaggregation [117].…”
Section: Gerinnungshemmungunclassified
“…Venoms from other animals are also reported; the venoms of centipedes [10], scorpions [11,12], fishes [13,14], and caterpillars [15], including microbial toxins [16]. The great potential for molecules derived from animal venoms as drug leads was also reviewed [17], and the antimicrobial [18], anticoagulant [19,20], and analgesic [21,22] effects have been highlighted in original studies reported here.…”
mentioning
confidence: 94%